Broadband generation of perfect Poincaré beams via dielectric spin-multiplexed metasurface - Mingze Liu (Nature Portfolio, 2021)
Well-controlled Poincaré beams are potentially useful in optical communications applications. Here, the authors present phase-only metasurfaces that generate broadband, perfect Poincaré beams in the visible, with radius independent of the topological number.